Cephalometric findings in nine individuals with richieri-costa-pereira syndrome - Oliveira Pinto, Rayane De; Peixoto, Adriano Porto; Santos Pinto, Ary Dos [UNESP]; Costa, Antonio Richieri; Zechi-Ceide, Roseli Maria; Ozawa, Terumi Okada; Silva Dalben, Gisele Da (Wolters Kluwer, 2018)
The Richieri-Costa-Pereira syndrome (RCPS) is an autosomal-recessive acrofacial dysostosis caused by mutations in EIF4A3, characterized by mandibular cleft comprising other craniofacial anomalies and limb defects such as cleft palate/Robin Sequence, microstomia, absence of mandibular central incisors, minor ear anomalies, clubfeet and first and 5 ray defects. The findings from this study are useful for better understanding the morphological consequences of disorders of EIF4A3, and having a better picture of the anatomic characteristics of the syndrome for a better therapeutic planning. Twenty-four angular and linear variables were measured to assess anteroposterior and vertical (superior- inferior) position of the cranial base, maxilla, mandible, and facial profile. The cephalometric radiographic analysis was performed on 9 individuals with RCPS, obtained at a mean age of 10.3 years, and compared with randomly selected age-matched 9 controls, without clefts and with well-balanced faces, with mean age of 10.6 years (both groups range 8.1 to 13.7 years). t test was used for analysis of means and Levene test for equality of variances. The syndrome group presented severe mandibular hypoplasia and retrognathism (P=0.009, P=0.001), greater facial convexity (N'PnPog and N'SnPog, P<0.05) in syndrome group compared with the control group (P=0.003, P=0.004). In conclusion, in the RCPS group, most craniofacial defects affect the lower facial third, considering the severely affected mandible. Copyright copy ;2018 by Mutaz B. Habal, MD.
Keywords: Craniofacial abnormalities; limb deformities,Micrognathism; Richieri-Costa-Pereira syndrome